Mitochondrial Single-stranded DNA-binding Protein Is Required for Mitochondrial DNA Replication and Development in Drosophila melanogaster - Maier, Dieter (The American Society for Cell Biology, 2001)
The discovery that several inherited human diseases are caused by mtDNA depletion has led to an increased interest in the replication and maintenance of mtDNA. We have isolated a new mutant in the lopo (low power) gene from Drosophila melanogaster affecting the mitochondrial single-stranded DNA-binding protein (mtSSB), which is one of the key components in mtDNA replication and maintenance. lopo(1) mutants die late in the third instar before completion of metamorphosis because of a failure in cell proliferation. Molecular, histochemical, and physiological experiments show a drastic decrease in mtDNA content that is coupled with the loss of respiration in these mutants. However, the number and morphology of mitochondria are not greatly affected. Immunocytochemical analysis shows that mtSSB is expressed in all tissues but is highly enriched in proliferating tissues and in the developing oocyte. lopo(1) is the first mtSSB mutant in higher eukaryotes, and its analysis demonstrates the essential function of this gene in development, providing an excellent model to study mitochondrial biogenesis in animals.